Reconstructing Sustainable Outdoor Learning Environment in Malaysia from the Understanding of Natural School Design and Approaches in Indonesia - Nurakmal, Abdullah@ Goh Tuo Ho; Utaberta, Nangkula; Spalie, N.; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2011)
With current development in the pedagogy of teaching and learning approaches in the world, not many studies have been done on outdoor learning in Malaysia. Most of the study was focusing on the development of curriculum and the delivery of knowledge but not many writing and approaches has been done to see outdoor learning as one of the alternative methods of learning in school design. This paper tries to briefly explain the philosophy and approaches of one of the alternative school in Indonesia which is the Natural school or Sekolah Alam which grow tremendously fast in Indonesia. With its unique methods and learning philosophy, this Toto Chan’s style of learning has been considered one of the fastest growing alternative school in Indonesia. With its successful attempt in grooming unordinary children this school has proofed to be the most effective implementation of outdoor learning study methods in Indonesia. The discussion itself will consist of four (4) main parts First part will discuss on the current problem and situation in teaching and learning in Malaysia, while the second part will try to explore and review on the definition of outdoor learning with its importance and character in learning environment. The third part will focused on the lesson from Natural School approaches and philosophy of learning while the last part will do some analysis and comparison which result on the suggestion and recommendation for outdoor learning facilities design in Malaysia.